PUBLIC SMOKING HEARING READINESS (Tufts Archival Research Center, 2007)
Marginalia; Confidential; Report from Susan Stuntz detailing the actions needing to be carried out before a public smoking hearing. Details the arguments that should be used against Senator Hatch's and Senator Mitchell's legislation for bans on smoking and issues of clean indoor air. Addresses issues related to banning smoking on airplanes. Urges speakers to focus on the need for increased ventilation systems to help with the issue of secondhand smoke.